PELAKSANAAN KEGIATAN EKSTRAKURIKULER FUTSAL DI SMK MUHAMMADIYAH 1 PEKANBARU - Janizan Saputra Ramadan; Zainur Zainur; Agus Sulastio (Jurnal Online Mahasiswa (JOM) Bidang Keguruan dan Ilmu Pendidikan, 2023)
Abstract: The aim of the research is to find out the implementation of futsal extracurricular activities at SMK Muhammadiyah 1 Pekanbaru. The location of this research will be carried out at Futsal Fishermen which is located at Jl. Fishermen, Sri Meranti, Rumbai, Pekanbaru. Overall the level of futsal extracurricular implementation at SMK Muhammadiyah 1 Pekanbaru which is in the very good category is 6 people at 28.57%, for the good category is 15 people at 71.43% and for the sufficient and not good category is 0% with no frequency in class intervals the. Based on the results, the level of futsal extracurricular implementation at SMK Muhammadiyah 1 Pekanbaru is in the Good category with an average result of 73.76%.Keywords: Futsal Extracurricular Activities